Pengaruh Model Pembelajaran Make A Match Berbantuan Media Wordwall Dilengkapi Video Animasi Terhadap Hasil Belajar Siswa - Vivien Adinda Kornelis , Vindri; Makaborang, Yohana; Ndjoeroemana, Yohana (Jurnal Biogenerasi, 2024)
Based on interviews and observations, the problems found show that learning is less varied, the use of textbooks and printed materials as learning resources, which is less interactive has an impact on the learning outcomes of Natural Sciences (IPA). The purpose of this study is to determine the influence of the Make a Match type cooperative learning model assisted by wordwalls equipped with animated videos on learning outcomes. The research is of the type of experimental research and comparative quantitative approach. It consists of two classes, namely the control class and the experimental class. The stages of research: preparation, implementation and completion. The sample in this study was 30 students in class IX A and 30 people in Class IX B as an experimental class. The data collection techniques and instruments used are tests and questionnaires. The data analysis techniques used are Validity and reliability tests, descriptive analysis . The results of the study can be seen from the comparison of the average score of meeting 1 of the control class of 52.66 (pretest), 68.32 (posttest) and the experimental class of the average score obtained 61.33 (pretest), 84.33 (posttest). while in meeting 2 the average value of the control class was 56.66 (Pretest), 66.66 (Posttest) and the experimental class was 60.33 (Pretest), 83.33 (Posttest). Sig (2-tailed) 0.000 means that the value < 0.05 so that H0 is rejected and H1 is accepted. It can be concluded that the Make A Match learning model assisted by Wordwall media equipped with animated videos has a significant effect on the learning outcomes of students in class IX B which is an experimental class at SMP Negeri 1 Pandawai.